Power module thermal cycling tester for in-situ ageing detection. (September 2017) - Pougnet, Ph.; Coquery, G.; Lallemand, R.; Makhloufi, A.
Abstract: The success of the electric car depends heavily on battery technology and on compact, reliable and efficient power converters in which power modules are a key element. Power Module technology is evolving rapidly. New semiconductor chips are developed to improve electrical performance and reduce power losses. Innovative design architectures are introduced to improve thermal management. Before mass production launch, the performance and lifetime of these technological innovations needs to be evaluated to respect the longer warranty requirements. This is usually achieved by Accelerated Testing. In this case, the effect of thermal cycles on the lifetime of power modules is usually studied by placing unpowered power modules in a thermal chamber and checking that their performance matches the specification after a given number of thermal cycles. However this method provides no information on the power module performance degradation due to cyclic thermal stresses. The Thermal Cycling Tester presented in this paper reproduces the stresses created in use conditions by environmental thermal cycles. This approach makes it possible to monitor ageing by applying power cycles periodically and measuring thermal and electric parameters. These results are then combined with mechanical and acoustic microscopy characterizations and finite element modeling results to provide a better understanding of the failure mechanisms.